Simulated Obstructive Sleep Apnea Increases P-Wave Duration and P-Wave Dispersion - Gaisl, Thomas; Wons, Annette M.; Rossi, Valentina; Bratton, Daniel J.; Schlatzer, Christian; Schwarz, Esther I.; Camen, Giovanni; Kohler, Malcolm (PloS one, 2016)
A high P-wave duration and dispersion (Pd) have been reported to be a prognostic factor for the occurrence of paroxysmal atrial fibrillation (PAF), a condition linked to obstructive sleep apnea (OSA). We tested the hypothesis of whether a short-term increase of P-wave duration and Pd can be induced by respiratory manoeuvres simulating OSA in healthy subjects and in patients with PAF. 12-lead-electrocardiography (ECG) was recorded continuously in 24 healthy subjects and 33 patients with PAF, while simulating obstructive apnea (Mueller manoeuvre, MM), obstructive hypopnea (inspiration through a threshold load, ITH), central apnea (AP), and during normal breathing (BL) in randomized order. The P-wave duration and Pd was calculated by using dedicated software for ECG-analysis. P-wave duration and Pd significantly increased during MM and ITH compared to BL in all subjects (+13.1 ms and +13.8 ms during MM; +11.7 ms and +12.9 ms during ITH; p<0.001 for all comparisons). In MM, the increase was larger in healthy subjects when compared to patients with PAF (p<0.05). Intrathoracic pressure swings through simulated obstructive sleep apnea increase P-wave duration and Pd in healthy subjects and in patients with PAF. Our findings imply that intrathoracic pressure swings prolong the intra-atrial and inter-atrial conduction time and therefore may represent an independent trigger factor for the development for PAF.